PADANAN TERJEMAHAN MODALITAS EPISTEMIK DALAM KOMIK KAGUYA-SAMA, LOVE IS WAR - Andrean Afrinaldo; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the translation of epistemic modality. The purpose of this study to explain the equivalent epistemic modality in Japanese comics on Indonesian translations. The data is a epistemic modality sentence taken from the Kaguya-sama, Love Is War comics. This is a qualitative research with a descriptive approach. The results of the analysis from Narrog's theory, it has been found that epistemic modalities be classified into epistemic necessity, epistemic possibility, speculative darou, and Inferential evidentials.Keywords: Epistemic Modality, Equivalent